Research on Several Inspection Methods to Determine the Sequence of Photocopying and Stamping - Jing Wang (Journal of Forensic Science and Medicine, 2015)
Determining the sequence of document production and stamping is one of the most important issues in the field of questioned document identification. In China, whether a contract or a document is legal or not, highly depends on the relationship between the generation time of the document's content and its stamping. Usually, a formal (legal) document would become effective once a seal is affixed, and normally, the content of the document is generated first and then subsequently stamped after being approved by the relevant personnel. Therefore, correctly identifying the sequence used to produce a document is necessary to determine whether it is authentic or whether it may have been forged. However, because of the interference of many factors, the identification of such kind of forged documents has long been considered one of the most difficult technical issues in the field of questioned document identification. In this work, four nondestructive approaches to determine the order of photocopying and stamping were investigated: The stereomicroscope method, fluorescence microscopy, the three-dimensional pseudo-color method, and the contour ring method. Each method is associated with its own advantages and disadvantages, but all have been shown to produce some useful results relevant for determining the sequence of photocopying and stamping.